Identification of Lasiodiplodia pseudotheobromae causing mango dieback in Korea. Issue 2 (3rd April 2017) - Kwon, Jin-Hyeuk; Choi, Okhee; Kang, Byeongsam; Lee, Yeyeong; Park, Jiyeong; Kang, Dong-Wan; Han, Inyoung; Kim, Jinwoo
Abstract: Mango ( Mangifera indica ) is an economically important fruit grown in tropical regions. Mango cultivation has increased in Korea as the fruit has become more popular; however, the majority of the fruit is imported. Mango dieback was observed for the first time in July 2016, in Tongyeong, South Korea. The aim of the present study was to identify the causal pathogen. Identification of the fungus was based on morphological and cultural characteristics, and sequencing of the internal transcribed spacer rRNA region and gene encoding translation elongation factor 1-alpha. A phylogenetic analysis of the sequences confirmed that the fungus isolated from diseased mango plants was Lasiodiplodia pseudotheobromae . Koch's postulates were completed by pathogenicity tests conducted on healthy leaves, fruit and whole plants. Based on the morphological characteristics, pathogenicity tests, and molecular identification, the causal fungus was identified as L. pseudotheobromae . This is the first report of mango dieback caused by L. pseudotheobromae in Korea. The recent occurrence of the disease indicates that the fungus poses a potential threat to mango production in Korea.